Emotion, Place and Weaponisation of the Truth: The Bloody Sunday Trust and the Search for Justice. Issue 375 (7th February 2022) - Petropoulos, Naomi
Abstract: On 30 January 1972 in Derry/Londonderry, a march protesting against the introduction of internment without trial ended with the deaths of thirteen demonstrators. The findings of the initial public inquiry, dubbed the 'Widgery Whitewash', resulted in decades‐long campaigning that still continues to this day. This article contextualises the events of Bloody Sunday and subsequent public inquiries while also exploring the evolution of the Bloody Sunday Justice Campaign into the Bloody Sunday Trust. It explores the Trust's use of emotion in its presentation as well as its choice of location for its own Museum of Free Derry. Finally, it combines observations of the museum with public history principles such as public outreach and community narratives to analyse whether or not the Trust's campaign and aims constitute a weaponisation of the truth. The article argues that weaponisation of the truth, rather than implying violence or confrontation, is a carefully constructed truth that has been deployed in the pursuit of justice. It concludes that the combination of significant geographical placement, the emotion evoked within and the strong sense of place presented by the Museum of Free Derry has successfully contradicted the initial Widgery Inquiry's findings. Also, the carefully designed aims of the Bloody Justice Campaign, along with the curation and presentation within the museum, have instituted a successful weaponisation of the truth in the defence of the victims and their families' reputations while providing the platform for the pursuit of the campaign's final aim, the prosecution of those soldiers who fired the fatal shots.